RATE OF WATER EXCHANGE BETWEEN AL(C2O4) (H2O)+4 (AQ) COMPLEXES AND AQUEOUS SOLUTIONS DETERMINED BY 17O-NMR SPECTROSCOPY - Phillips B.L.; Neugebauer Crawford S.; Casey W.H. (My University, 1997)
Substitution of an oxalate molecule for two inner-coordination-sphere waters of Al(H2O)3+6 (aq) enhances, by a factor of ~ 102, the rate of exchange of water molecules from the inner-coordination sphere to the bulk solution. The rate parameters for chemical exchange are: k298ex = 109 s-1, ΔH\PG = 68.9 +/- 2.4 kJ/mol, and ΔS\PG = 25.3 +/- 6.7 J/mol/K, measured via dynamic 17O-NMR. This reactivity enhancement of coordinated waters by oxalate results from a change in bonding between Al(III) and oxygens throughout the complex upon ligation by oxalate. A similar process has been proposed to explain ligand-enhanced dissolution of oxide minerals (e.g., Stumm, 1991; Casey and Ludwig, 1995; Phillips et al., 1997) where a stable adsorbate increases the flux of metals from a surface. These new rate coefficients for aluminum-oxalate complexes, along with previous work on aluminum-fluoride complexes, show a correlation with the respective equilibrium constants similar to that obtained by Ludwig et al. (1995, 1996).